“The Impact of Vegan Labels on Consumer Behaviour” - Mohana, Rami (2024)
The purpose of this bachelor's thesis is to examine the impact of vegan labelling on consumer behaviour in the Czech Republic. The primary objective is to investigate how vegan food labelling influences consumer purchasing decisions and perceptions, particularly in identifying any potential drawbacks such as reduced willingness to pay for vegan products and difficulty distinguishing them from non-vegan products. The thesis is divided into two sections: a theoretical section covering veganism, consumer behaviour, labelling, and areas for future research, and a research section covering methodology, analysis, and results. Findings indicate that while there is a high recognition of vegan labels among consumers, this does not consistently translate into a higher willingness to pay, revealing a significant gap between label recognition and purchasing behaviour. Unexpectedly, the study found no significant correlation between gender and awareness of veganism, which contrasts with the assumption that female consumers might be more receptive to vegan labelling. The research also highlights a drawback: consumers often confuse vegan labels with general health and organic claims, which can lead to misinformed purchasing decisions. In conclusion, while vegan labelling has a noticeable impact on consumer awareness, it faces challenges in converting this awareness into consistent purchasing behaviour. This underscores the need for clearer labelling and education to better align consumer understanding with the ethical and health benefits of vegan products.